Developing Zoonoses-Themed Reading Materials for EFL Students Within the Emancipated Curriculum Framework - Armanda, Muhamad Laudy; Waly, Muchamad Muchibbuddin; Andika, Jeffri Dian; Pratiwi, Dwiyani; Yulia, Yuyun (JOLLT Journal of Languages and Language Teaching, 2025)
Although the notion of establishing global education has existed since the early 21st Century, the majority of current EFL textbooks neglect global issues as teaching content. However, existing studies on the implementation of the current Emancipated Curriculum have yet to incorporate authentic materials related to these topics, which remain significantly underexplored. In such a manner, this study introduced a supplementary reading material integrated with zoonoses topic as a part of global health issues nowadays. Utilizing a mixed-method approach to accomplish an ADDIE model, the study presents clear DBR stages. Various instruments, such as questionnaires, interviews, tests, and digital artifacts, were used. Half of the student population was obtained as samples (N=63), and an English teacher participated in this study. The major findings underscore the significant difference in the experiment group studentsâ€™ reading skills based on t-value (7.011) > Î± (0.05). To a certain extent, user responses (88%) and module evaluation (95%) toward the product were considered very worthy or eligible to be employed for teaching reading in English classrooms. Apart from the empirical evidence, the study offers practical insights for English teachers in similar areas, highlighting the potential of proposing global issue topics to bridge the students' knowledge, skills, and awareness of real-world situations. Shortly, this will contribute valuable direction for the future development of English teaching materials.Â 